Україна в інтеграційних проектах країн заходу і сходу - Панасюк, В. А.; Panasyuk, V; Панасюк, В. А. (My University, 2011)
This paper studies the geopolitical struggle of the leading integration structures of East and West for the dominant inﬂ uence on the Ukrainian state. We study ways to integrate Ukraine into the world community. Characterized model of integration policy. The features of European and Eurasian paradigm of integration processes.
Панасюк В. А. Україна в інтеграційних проектах країн заходу і сходу / В. А. Панасюк // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С. 105- 115.
Keywords: інтеграційні процеси.інтеграція України.; интеграционные процессы. интеграция Украины.; іntegratsіynі protsesi.іntegratsіya Ukraine